Changes in the pattern of Kaposi's sarcoma at Ocean Road Cancer Institute in Tanzania (2006–2011). (June 2015) - Koski, Lia; Ngoma, Twalib; Mwaiselage, Julius; Le, Lynne; Soliman, Amr S
Tanzania has high human immunodeficiency virus and human herpes virus-8 rates linked to Kaposi's sarcoma. We conducted a study at the Ocean Road Cancer Institute in Dar es Salaam, Tanzania to examine changes in proportions of Kaposi's sarcoma to all cancers over the period (2006–2011) of increased acquired immune deficiency syndrome management by anti-retroviral therapy. We included 1504 Kaposi's sarcoma cases from Ocean Road Cancer Institute and abstracted information regarding age, gender, human immunodeficiency virus and tuberculosis, anti-retroviral therapy duration and Kaposi's sarcoma lesions. Male Kaposi's sarcoma patients (59.6%) were older (42.1 ± 11.5 years) than women (40.4%) (36.2 ± 9.6 years). Kaposi's sarcoma proportions declined from 10.1% in 2003 to 7.4% in 2011. Being a woman was associated with increased oral and generalized lesions and higher numbers of lesion locations (odds ratio [OR] = 2.17, 95% confidence interval [CI]: 1.35, 3.51; OR = 1.49, CI: 1.08, 2.06; OR = 1.06, CI: 0.79, 1.41, respectively). Tuberculosis was associated with oral, generalized and number of lesion locations (OR = 2.08, CI: 1.10, 3.93; OR = 2.06, CI: 1.28, 3.33; OR = 1.88, CI: 1.19, 2.97, respectively). Anti-retroviral therapy duration showed a protective effect with oral, generalized and number of lesion locations (OR = 0.55, CI: 0.33, 0.91; OR = 0.73, CI: 0.52, 1.01; OR = 0.89, CI: 0.67, 1.18, respectively). With increasing number of patients receiving prolonged anti-retroviral therapy, future studies should investigate long-term effect of anti-retroviral therapy and tuberculosis in Tanzania and countries with human immunodeficiency virus infection.